Initial experience with the subcutaneous implantable cardioverter‐defibrillator in a single Japanese center. Issue 4 (31st March 2017) - Nishii, Nobuhiro; Tachibana, Motomi; Morimoto, Yoshimasa; Kawada, Satoshi; Miyoshi, Akihito; Sugiyama, Hiroyasu; Nakagawa, Koji; Watanabe, Atsuyuki; Nakamura, Kazufumi; Morita, Hiroshi; Ito, Hiroshi
Abstract: Background: The subcutaneous implantable cardioverter‐defibrillator (S‐ICD) is recognized as a viable alternative to the transvenous ICD. The safety and efficacy of this device has been demonstrated in Western countries, but studies with S‐ICD implantation in Japanese patients have not been reported. Methods and results: Twelve patients received an S‐ICD implant in our institute between February and September 2016. All S‐ICDs were successfully implanted without complications. One appropriate and one inappropriate therapy was identified. Conclusions: S‐ICD implantation appears to provide a viable alternative to transvenous ICD implantation for some Japanese patients. However, we should perform careful follow‐up of patients to eliminate inappropriate therapy.